Comparison of Spot Urine vs 24-Hours Urine in Assessment of Proteinuria in Patients with Type 2 Diabetes Mellitus - Abideen, Muhammad Zain; Yusuf, Rizwan; Barki, Zaboor; Khan, Muhammad Ali; Umar, Nadeem; Nadeem, Minahil (Pakistan Armed Forces Medical Journal, 2025)
Objective: To assess the correlation between spot urine test (Spot Protein/Creatinine Ratio) and 24-hours urine protein analysis in assessing proteinuria among patients with Type 2 diabetes.Study Design: Cross-Sectional Study.Place and Duration of Study: Department of Medicine, Combined Military Hospital, Abbottabad Pakistan, from Oct 2022 to Mar 2023.Methodology: Eighty patients of either gender with diagnosed Type 2 Diabetes Mellitus presenting to CMH Abbottabad during study period with evidence of proteinuria were included in the study. 24-hours urine sample was obtained for analysis of 24 hours protein excretion. Urine was also tested for spot protein creatinine ratio in all patients. Association of 24-hour urine and spot urine protein levels was observed and represented by ROC curve and Pearson's correlation.Results: Total 80 diabetic patients with proteinuria analyzed with mean age of 53.51±6.34 years including 45(56.3%) males and 35(43.8%) females. The mean duration of diabetes was 7.75±1.95 years with mean fasting sugar 183.88±36.33 mg/dL and HbA1c 9.46±1.30%. The observed mean 24-hour urinary protein was 1194.60±398.39 mg/day and mean spot uPCR was 1005.49±446.84 mg/mmol. An affirmative correlation was noted in 24-hours urine protein and uPCR (r value= 0.604; p